Serum Folate, Vitamin B-12, Vitamin A, γ-Tocopherol, α-Tocopherol, and Carotenoids Do Not Modify Associations between Cadmium Exposure and Leukocyte Telomere Length in the General US Adult Population. Issue 4 (8th March 2017) - Nomura, Sarah JO; Robien, Kim; Zota, Ami R
Abstract: Background: Leukocyte telomere length (LTL) is a biomarker of the aging process and is associated with the risk of chronic disease. Higher exposure to cadmium may be associated with shorter LTL, and adequate nutrient concentrations may be associated with longer LTL; however, the potential interaction between metals and nutrients on LTL has yet to be examined. Objectives: The objective of this study was to evaluate whether serum concentrations of vitamins and carotenoids were associated with LTL, and whether they modified the association between blood cadmium and LTL in the US NHANES (1999–2002). Methods: We evaluated cross-sectional associations between LTL and serum concentrations of vitamin A, γ-tocopherol, α-tocopherol, folate, and vitamin B-12 (1999–2002; n = 7458) and α-carotene, β-carotene, β-cryptoxanthin, lutein + zeaxanthin, and lycopene (2001–2002; n = 4018) in a nationally representative sample of US adults (≥20 y of age) with the use of multivariable linear regression. We further investigated whether vitamin and carotenoid concentrations modified associations between blood cadmium and LTL with models stratified by serum nutrient concentrations and the inclusion of an interaction term. Results: Blood cadmium was inversely associated with LTL (percentage of LTL difference per 1 μg/L = −3.74; 95% CI: −5.35, −2.10). Serum vitamin A was positively associated (percentage of LTL difference per 1 μg/L = 4.01; 95% CI: 0.26, 7.90) and γ-tocopherol was inversely associated (percentage of LTL difference per 1 μg/dL = −2.49; 95% CI: −4.21, −0.73) with LTL. Serum folate ( P -trend = 0.06) and α-tocopherol ( P -trend = 0.10) were marginally positively associated with LTL, whereas vitamin B-12 ( P -trend = 0.78) was not associated with LTL. Serum carotenoids were generally positively associated with LTL. Serum vitamin and carotenoid concentrations did not modify blood cadmium and LTL associations ( P -interaction > 0.10). Conclusions: Results from this cross-sectional study suggest that exposure to cadmium and certain nutrients may be associated with LTL in US adults, but the serum concentrations of the vitamins and carotenoids evaluated did not modify cross-sectional associations between cadmium exposure and LTL.